A Sweden in Miniature, a Sweden in a Funhouse Mirror. Slyngstad Events as Social Satire on the Late Folkhem Period - Żmuda-Trzebiatowska, Magdalena (Nordlit, 2023)
The novel Slyngstad Events (2002) by Unni Drougge can be classified as a tall tale, i.e. a fictional, humorous story that is mostly meant to entertain. At the same time, the book contains a great deal of contemporary criticism: Åsabygden, a fictional area in Skåne where the story is set, suffers from the same problems as the late-modern Swedish welfare society in general and can be regarded as a Sweden in miniature. By analysing the novel’s strong and expressive characters, I want to show that the novel is not just an entertaining tale, but can be regarded as a social satire in which the individual actors represent different ways of life and values, but above all different weaknesses and shortcomings of citizens in the welfare state. In a broader sense, Slyngstad Events also appears as a story about a Sweden that is no longer a happy folkhem and a model country, but is being transformed into its opposite, a bizarre monster country, something I develop by interpreting the novel against the background of the various historical accounts of the Swedish folkhem.